Comparison of Anterior Cervical Discectomy and Fusion versus Posterior Cervical Foraminotomy in the Treatment of Cervical Radiculopathy: A Systematic Review - Liu, Wei‐jun (Orthop Surg, 2016)
Controversy remains over whether anterior cervical discectomy and fusion (ACDF) or posterior cervical foraminotomy (PCF) is superior for the treatment of cervical radiculopathy. We therefore performed a systematic review including three prospective randomized controlled trails (RCT) and seven retrospective comparative studies (RCoS) by searching PubMed and EMBASE. These studies were assessed on risk of bias according to the Cochrane Handbook for Systematic Reviews of Interventions, and the quality of evidence and level of recommendation were evaluated according to the GRADE approach. Clinical outcomes, complications, reoperation rates, radiological parameters, and cost/cost‐utility were evaluated. The mean complication rate was 7% in the ACDF group and 4% in the PCF group, and the mean reoperation rate was 4% in the ACDF group and 6% in the PCF group within 2 years of the initial surgery. There was a strong level of recommendation that no difference existed in clinical outcome, complication rate and reoperation rate between the ACDF and the PCF group. There was conflicting evidence that the ACDF group had better clinical outcomes than the PCF group (one study with weak level of recommendation). PCF could preserve the range of motion (ROM) of the operated segment but did not increase the ROM of the adjacent segment (weak level of recommendation). Meanwhile, the average cost or cost‐utility of the PCF group was significantly lower than that of the ACDF group (weak level of recommendation). In conclusion, the PCF was just as safe and effective as the ACDF in the treatment of cervical radiculopathy. Meanwhile, PCF might have lower medical cost than ACDF and decrease the incidence of adjacent segment disease. Based on the available evidence, PCF appears to be another good surgical approach in the treatment of cervical radiculopathy.